Perang dan Kekerasan Atas Nama Agama dalam Wacana Ilmiah - Ustadi Hamsah (UIN Sunan Kalijaga Yogyakarta, 2012)
Religion always offers both peace and steady, but negates war and violence. In the history of human civilization, religion is present in the course of human life. Religion, in one side, serves as a cure in the hard situation of human history such as starvation, death and disaster, however, either war or violence is ironically triggered by human’s view on religion to justify violence in the name of religion. The phenomenon signifies the bold topic of human history, religion and violence. Applying the sociology of religion approach, this paper tries to explore how the contruction of human thought is present related to their views on religion, and how the position of religion in the context of war and violence in the lines of their history.